Adherence to cancer screening guidelines in Australian survivors of allogeneic blood and marrow transplantation (BMT). (25th April 2016) - Dyer, Gemma; Larsen, Stephen R.; Gilroy, Nicole; Brice, Lisa; Greenwood, Matt; Hertzberg, Mark; Kabir, Masura; Brown, Louisa; Hogg, Megan; Huang, Gillian; Moore, John; Gottlieb, David; et al.
Abstract: Allogeneic Blood and Marrow Transplant (BMT) survivors are at high risk of secondary cancers. Although current guidelines endorse survivors following Country‐specific general population screening recommendations to mitigate this risk, little is known about cancer screening adherence in Australian BMT survivors. We conducted a cross‐sectional survey of 441 BMT survivors who were >1 year post transplant, to explore rates of screening for secondary cancers and to identify barriers to cancer screening recommendations. Survey instruments included the Sydney Post‐BMT Survey, FACT‐BMT, DASS 21, The Chronic Graft versus Host Disease (GVHD) Activity Assessment–Patient Self‐Report (Form B), the Lee Chronic GVHD Symptom Scale, Fear of Cancer Recurrence Scale, and The Post Traumatic Growth Inventory. Fifty‐seven percent of respondents were male, median age 54 years, and 40% were> 6 years post‐BMT. Rates of cancer screening adherence were as follows: cervical 63.4%, breast 53.3%, skin 52.4%, and bowel 32.3%. Older BMT survivors and those >2 years post transplant were more likely to undergo cancer screening. Improved quality of life was associated with screening for skin, breast, and cervical cancer. Fear of cancer recurrence negatively impacted on cervical screening. For those who had not undergone screening, the majority reported not being advised to do so by their treatment team. This study is the largest and most comprehensive to date exploring cancer screening adherence in BMT survivors in Australia. These data provide the basis for health service reform to better meet the needs of BMT survivors and provide evidence to support counseling and education of both patients and professionals. Abstract : We conducted a cross‐sectional survey of 441 Blood and Marrow Transplant (BMT) survivors who were >1 year post transplant, to explore rates of screening for secondary cancers and to identify barriers to adherence with cancer screening recommendations. Rates of cancer screening uptake were as follows: cervical 63.4%, breast 53.3%, skin 52.4%, and bowel 32.3%. Improved quality of life was associated with screening for skin, breast, and cervical cancer. Fear of cancer recurrence negatively impacted on cervical screening. For those who had not undergone screening, the majority reported not being advised to do so by their treatment team.